A new species of Thismia (Thismiaceae) from Brunei Darussalam, Borneo - Dančák, Martin; Hroneš, Michal; Sochor, Michal; Kobrlova, Lucie; Hédl, Radim; Hrázský, Záboj; Vildomcová, Anna; Sukri, Rahayu Sukmaria; Metali, Faizah (Phytotaxa, 2013)
A new species of Thismia (Thismiaceae) from Borneo is described. Thismia hexagona was discovered in 2013 in lowland mixed dipterocarp forest in Ulu Temburong, Brunei Darussalam. The species is circumscribed, illustrated and its position within the Malesian species of the genus is characterised by insertion into the existing determination key. Its most conspicuous feature is bright yellow, sharply hexagonal flower annulus.